Hartoni HUBUNGAN KONSEP DIRI DENGAN TINGKAT KECEMASAN NARAPIDANA MENUNGGU HASIL PUTUSAN SIDANG DI RUTAN MAKO POLRES TEBO : HUBUNGAN KONSEP DIRI DENGAN TINGKAT KECEMASAN NARAPIDANA MENUNGGU HASIL PUTUSAN SIDANG DI RUTAN MAKO POLRES TEBO - Hartoni; Erfianan, Erma; Enopadria, Costarin (Lembaga Marwah Rakyat, 2024)
Social life in prison will also influence the mental development of prisoners. Related to the bad stereotype of society which has labeled criminals for prisoners, it will affect the psychological conditions such as prisoners' anxiety waiting for the results of the trial decision at the Tebo Police Headquarters Detention Center. Knowing the Relationship between Self-Concept and the Anxiety Level of Prisoners Waiting for the Results of the Trial Decision at the Tebo Police Mako Detention Center. This research uses a cross-sectional approach. The population in this study were prisoners awaiting the results of the trial verdict at the Tebo Police Headquarters Detention Center. The sample in this study was 53 prisoners. The measuring tool used to measure anxiety levels is with a questionnaire. Data analysis used the Chi-Square test. Research shows that of the 53 respondents who described their self-concept, the majority (73.6%) had high self-concept and anxiety, and the majority (86.8%) experienced moderate anxiety. Based on the scale test using the chi-square test, p (0.000) or p <0.05 was obtained. This means that there is a significant relationship between self-concept and prisoners' anxiety waiting for the results of the trial decision at the Tebo Police Headquarters Detention Center. For institutions to improve the quality and quality of institutional students regarding the self-concept of prisoners who are waiting for the results of the court's decision